INHIBITION OF CELLULAR INVASION AND INDUCTION OF ANOIKIS IN MOUSE MELANOMA CELLS BY AN ANTI-INFLAMMATORY AGENT DTCM-GLUTARIMIDE - A. Kaneda; Sh. Kh. Gantsev; K. Umezawa (Креативная хирургия и онкология, 2017)
Previously, we designed DTCM-glutarimide as a novel anti-inflammatory agent inhibiting macrophage activation. It also showed anti-inflammatory activity in vivo. In the present research, we evaluated the  anti-metastatic activity of this agent using  mouse  melanoma B16-F10 cells. DTCM-glutarimide inhibited  the cellular invasion in the Matrigel chamber assay, lowering matrix metalloproteinase 9 (MMP9) expression. It also induced  anoikis rather than  apoptosis in polyHEMA-coated plates.  It increased Bax and decreased Bcl-XL  expressions,  and  activated p53  lowereing  the  MDM2 expression. Thus, DTCM-glutarimide was found to inhibit cellular invasion and to induce anoikis in B16-F10 cells. It is non-toxic, and easily prepared, therefore, is considered to be a new candidate of anti-metastasis agent.